THE ROLE AND FUNCTION OF THE DA'I IN THE PSYCHOLOGICAL PERSPECTIVE OF DAKWAH - Kholis Kohari; Mohammad Adnan; Zamakhsyari Abdul Majid; Farhat Abdullah (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2022)
This paper discusses the role and function of the dai in the perspective of da'wah psychology. Da'wah is the duty of every Muslim. As preachers of course we want to be successful in achieving the task of da'wah. One form of success in da'wah is a change in a person's mental attitude. Da'wah psychology guides da'wah activities, so the purpose of da'wah psychology in the role and function of da'wah is to provide views about the possibility of changing the psychological behavior or mental attitude of the target of da'wah in accordance with the pattern of life desired by religious teachings. The role and function of the dai as a da'wah interpreter is one of the factors in da'wah activities which occupies a very important position in the success or failure of da'wah activities. Dai professionals who specialize in the field of da'wah, should have a good personality to support the success of da'wah, both spiritual and physical. The results to be obtained with the knowledge of this paper, it is hoped that we can carry out the task of da'wah with a psychological approach so that it is well understood the role and function of a dai as a preacher and the condition of the object of da'wah as mad'ū. Tulisan ini membahas tentang peran dan fungsi dai dalam perspektif psikologi dakwah. Dakwah merupakan kewajiban setiap muslim. Sebagai dai tentu saja kita ingin mencapai kesuksesan dalam melaksanakan tugas dakwah. Salah satu bentuk keberhasilan dalam dakwah adalah berubahnya sikap kejiwaan seseorang. Psikologi dakwah memedomani kegiatan dakwah, maka tujuan psikologi dakwah dalam peran dan fungsi dai memberikan pandangan tentang mungkinnya dilakukan perubahan tingkah laku atau sikap mental psikologis sasaran dakwah sesuai dengan pola kehidupan yang dikehendaki oleh ajaran agama. Peran dan fungsi dai sebagai juru dakwah adalah salah satu faktor dalam kegiatan dakwah yang menempati posisi sangat penting dalam berhasil atau tidaknya kegiatan dakwah. Dai profesional yang mengkhususkan diri di bidang dakwah, seharusnya memiliki kepribadian yang baik untuk menunjang keberhasilan dakwah baik yang bersifat rohani atau yang bersifat fisik. Hasil yang ingin diperoleh dengan pengetahuan tentang tulisan ini, diharapkan kita dapat melaksanakan tugas dakwah dengan pendekatan kejiwaan sehingga dipahami dengan baik peran dan fungsi seorang dai sebagai mubalig dan kondisi objek dakwah sebagai mad‘ū.